(3GdNhUUI hGdJUMjMGJ GdgjcdjI(B((3BQGA hGJLGgGJ(B)s - (3VjGA eLjO(B, (3GdehShjs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2005)
(3GjOjhdhLjI GdOYhI GdQGgfI hQGA JbdjU OhQ GdbWGY GdYGe,bhGYO GbJUGOjGJ GdShb,EUdGM GdbWGY GdYGe,EYGOI GdgjcdI(B((3GdHjQjSJQhjcG(B)s
(3HHdjhZQGajG(B:(3U(B.122s
Keywords: (3GdbWGY GdNGUs; (3GdbWGY GdYGes